2014
DOI: 10.1124/jpet.114.217315
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Ca2+-Activated Cl Channel TMEM16A by the Inhibition of Histone Deacetylase in TMEM16A-Expressing Cancer Cells

Abstract: The Ca 21 -activated Cl 2 channel transmembrane proteins with unknown function 16 A (TMEM16A; also known as anoctamin 1 or discovered on gastrointestinal stromal tumor 1) plays an important role in facilitating the cell growth and metastasis of TMEM16A-expressing cancer cells. Histone deacetylase (HDAC) inhibitors (HDACi) are useful agents for cancer therapy, but it remains unclear whether ion channels are epigenetically regulated by them. Using real-time polymerase chain reaction, Western blot analysis, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…It has reported that AATB (4-(acetylamino)- N -[2-amino-5-(2-thienyl)phenyl]-benzamide) is a selective HDACi for HDAC1 and HDAC2 (half maximal (50%) inhibitory concentration (IC 50 ) = 7 and 49 nM for HDAC1 and HDAC2, respectively and IC 50 ≥ 10 μM for the other HDAC isoforms) [35]. In addition, in our previous study, inhibitory effects of target gene transcription by 30 nM and 300 nM AATB were very similar to those by HDAC1 and HDAC2 siRNAs, respectively [36]. The inhibitory effects of K Ca 1.1 transcription were demonstrated through the pharmacological blockade of HDAC1 and HDAC2 by 300 nM AATB ( n = 4, p < 0.01), whereas no significant changes were found by the respective inhibition of HDAC1, HDAC3, and HDAC6 by treatments with 30 nM AATB, 1 μM T247 [ N -(2-aminophenyl)-4-[1-(2-thiophen-3-ylethyl)-1 H -(1),(2),(3)triazol-4-yl]benzamide], and 1 μM NCT-14b [( S )- S -7-(adamant-1-ylamino)-6-(tert-butoxycarbonyl)-7-oxoheptyl-2-methylpropanethioate] for 48 h ( n = 4 for each, p > 0.05).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…It has reported that AATB (4-(acetylamino)- N -[2-amino-5-(2-thienyl)phenyl]-benzamide) is a selective HDACi for HDAC1 and HDAC2 (half maximal (50%) inhibitory concentration (IC 50 ) = 7 and 49 nM for HDAC1 and HDAC2, respectively and IC 50 ≥ 10 μM for the other HDAC isoforms) [35]. In addition, in our previous study, inhibitory effects of target gene transcription by 30 nM and 300 nM AATB were very similar to those by HDAC1 and HDAC2 siRNAs, respectively [36]. The inhibitory effects of K Ca 1.1 transcription were demonstrated through the pharmacological blockade of HDAC1 and HDAC2 by 300 nM AATB ( n = 4, p < 0.01), whereas no significant changes were found by the respective inhibition of HDAC1, HDAC3, and HDAC6 by treatments with 30 nM AATB, 1 μM T247 [ N -(2-aminophenyl)-4-[1-(2-thiophen-3-ylethyl)-1 H -(1),(2),(3)triazol-4-yl]benzamide], and 1 μM NCT-14b [( S )- S -7-(adamant-1-ylamino)-6-(tert-butoxycarbonyl)-7-oxoheptyl-2-methylpropanethioate] for 48 h ( n = 4 for each, p > 0.05).…”
Section: Resultsmentioning
confidence: 87%
“…They were maintained at 37 °C in 5% CO 2 with RPMI 1640 medium, Dulbecco’s modified Eagle’s (DMEM) medium, or Leibovitz’s L-15 medium containing 10% fetal bovine serum (Sigma, St. Louis, MO, USA) and a penicillin (100 units/mL)-streptomycin (0.1 mg/mL) mixture [36]. A cell viability assay using WST-1 (2-(4-Iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2 H -tetrazolium, monosodium salt), which is a colorimetric assay to measure the viable cell numbers by the cleavage of tetrazolium salts was performed according to our previous study [36]. Briefly, using a density of 10 5 cells/mL, cells were cultured in duplicate in 96-well plates for 0–4 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…T247 and T326 inhibited the growth of colon and prostate cancer cells (Suzuki et al 2013). In TMEM16A–expressing cancer cells, T247 also exerts a suppressive effect on cancer cell viability via downregulatingTMEM16A (Matsuba et al 2014). …”
Section: Anticancer Effect Of Hdac Inhibitorsmentioning
confidence: 99%